Sleep: sketch for the painting, now in the museum at Lille - Pierre Puvis de Chavannes (Wikimedia Commons, 1840)
Notice iconographique issue de Wikimedia Commons. Titre: Sleep: sketch for the painting, now in the museum at Lille. Drawing | Drawings
Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; illustration